THE ROLE OF THE VIRTUAL LABORATORY IN TEACHING STEM SCIENCES - Nodirbek Ruziyev Avazjon o’g’li (Prospects for innovative technologies in science and education, 2025)
This article analyzes the effectiveness of organizing education based on the STEM approach, in particular, teaching mathematics, biology, technology and physics through a virtual laboratory platform. It also considers the possibilities of obtaining real-time data through sensors and integrating them into the learning process. The article is aimed at forming interactivity, practical skills, interdisciplinary connections and a problem-oriented approach through the use of virtual tools in teaching, and is enriched with experimental results.